Greening the Heat Investigating the Impact of Vegetative Roofs on Thermal Regulation in Buildings - Domanický Ján (Selected Scientific Papers: Journal of Civil Engineering)
Climate and its protection, use of renewable energy sources, global warming, etc. As for the projection of buildings, this is nowadays the most watched aspect in the creation of the concept of each of them. Whether it is a new building or a reconstruction. Various subsidy aspects are set up for this issue. In general, we know subsidies for the renewal of buildings in the form of a subsidy for insulation. It is also possible to obtain a subsidy for resources, either in the form of a heat pump or photovoltaic panels. For apartment buildings, renovations are adapted in so-called packages or combinations. All this should serve to reduce the need for energy for heating as well as electricity. This work is rather passive in how this need can be reduced.